Anthropometric Study of Canthal Distances and Mouth Width Among Adults of Kalabari - Benwoke, W. I.; Amachree, E.P; Perebosigha, S.I; Bienonwu , E. O. (International Journal of Health Sciences, 2023)
Purpose: The face is considered to be the most crucial aspect to define the beauty of a particular individual. Therefore, the facial anatomy of different ethnic groups must be well understood for forensic studies, research, and also for surgery purposes. The purpose of this study is to establish normal values of canthal distances and mouth width parameters in adult Kalabaris in Rivers State, Nigeria, to determine sexual dimorphism and also to correlate them with age. Methodology: The study was conducted using a total of 315 participants, consisting of 163 females and 152 males, selected randomly from the various Kalabari communities, between the ages of 19 and 50. Participants were measured using a digital Vernier caliper. Findings: The data were collected and analysed using SPSS, and results were expressed in mean ± standard deviation. The mean values of inner canthal distance in adult males and females were 36.64 ± 1.81mm and 34.78 ± 3.25mm respectively. Mean values for outer canthal distance were 99.30 ± 3.63mm for males and 97.91 ± 4.45mm for females. The mean values for mouth width in males was 55.69 ± 5.58mm, whereas in females it was 53.92 ± 3.23mm. Unique Contribution to Theory, Policy and Practice: There is sexual dimorphism in the parameters measured, and it also showed significant positive relation with age, p < 0.05. Comparison with other population showed the mean values for the parameters in the adult kalabari population differ from them. Data obtained in this study would provide basis for application in forensics, maxillofacial surgery and clinical practice in Rivers State, Nigeria We recommend that the result of this study be used as a baseline data for future works and similar studies be done on other ethnic groups